Correlational study between Body Mass Index conditions in children and their parents in pediatric, adolescence, adulthood ages: Body Mass Index conditions in children and their parents in pediatric, adolescence, adulthood ages - Vitale, Elsa; Lupo, Roberto; Lezzi, Alessia; Caldararo, Cosimo; Rizzo, Alessandra; Zacchino, Simone; Lezzi, Pierluigi; Scupola, Giovanni; Calabrò, Antonino; Chetta, Giorgia; Corvace, Pietro; Ercolani, Maurizio; et al. (Progress in Nutrition, 2023)
Background and aim: The influence of individual parents depends on the age and sex of the child. Teenage boys, who have both overweight or obese parents, are more likely to be overweight themselves, but just having an obese mother is enough to increase the likelihood of a preschool boy are obese. To assess any correlations existed between BMI conditions in children related to their BMI parents' conditions, by considering their pediatric, adolescence and adulthood age. Methods: During 2020 and 2021 data were collected both from children, aged between 3 to 14 years old and their respective parents in the ambulatory setting. Additionally, it was assessed parent’s weight conditions, both for mothers and fathers during their pediatric, adolescent and adult ages, by only considered if there were: underweight, normal weight, overweight or obese, respectively. Results: 135 children were enrolled with their respective parents, too. Significant correlations were performed between BMI in children and their mothers’ conditions in pediatric age (ρ=0.196; p=0.025); between BMI in children and fathers, both during the adolescence (ρ=0.176; p=0.046) and the adulthood (ρ=0.184; p=0.037). Additionally, significant correlations were performed between BMI in children and their mothers’ conditions in pediatric age (ρ=0.196; p=0.025); between BMI in children and fathers, both during the adolescence (ρ=0.176; p=0.046) and the adulthood (ρ=0.184; p=0.037). Conclusions: Significant correlations emerged between the BMI of parents and that of children. The timely intervention on cases of obesity and severe overweight within family contexts could prevent the possibility not only of diseases related to these realities, but also an increased risk of becoming obese in the adulthood.